SOSIALISASI MENINGKATKAN IMUNITAS KESEHATAN IBU DI MASA PANDEMI DI LINGKUNGAN RW 07 KARANGBESUKI KOTA MALANG - Wilyati Agustina Bangun; Suhartatik Suhartatik; Titik Purwati (JPM PAMBUDI, 2021)
In 2020, the outbreak of a new virus that shocked the world, namely Coronavirus Disease (Covid 19). There are some ways to survive from the pandemic such as obeying government instructions and increase the immunity of body. The purpose of the community service is to provide counseling or social outreach, as well as provide education related to improving maternal health and immunity during the pandemic. The activities of Community Service cover several stages. First, coordinating about the Community Service Agenda with the Head of Neighborhood and Citizens Associations. Second, the executor team prepare some materials of socialization. Third, the executor team conduct the educational outreach. In conclusion, improving maternal health and immunity can be reached by consuming healty food, providing healthy life, and avoiding stress.